2020
DOI: 10.1371/journal.pone.0235480
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease in cats alters response of the plasma metabolome and fecal microbiome to dietary fiber

Abstract: The objectives were to determine the effects of feeding different fiber types to healthy cats and cats with chronic kidney disease (CKD) on plasma metabolites and the fecal microbiome. Methods A cross-over study within a split-plot design was performed using healthy (n = 10) and CKD cats [IRIS Stage 1 and 2; n = 10]. Cats were fed dry Prescription Diet ® k/d ® Feline with chicken, during a pre-trial period and then randomly assigned to two fiber treatments for 4 weeks each. Treatment foods were formulated simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 45 publications
2
49
1
1
Order By: Relevance
“…Several studies have shown limited effects of consumption of increased whole plant foods, including fiber, on gut microbial composition in humans [ 47 ]. Of note, there were no significant differences between healthy dogs and those with CKD in the fecal microbiome at baseline, consistent with the few changes observed in a similar study on cats [ 6 ]. Thus, it appears that gut microbial composition in the early stages of CKD in cats or dogs is not substantially different from the healthy state.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Several studies have shown limited effects of consumption of increased whole plant foods, including fiber, on gut microbial composition in humans [ 47 ]. Of note, there were no significant differences between healthy dogs and those with CKD in the fecal microbiome at baseline, consistent with the few changes observed in a similar study on cats [ 6 ]. Thus, it appears that gut microbial composition in the early stages of CKD in cats or dogs is not substantially different from the healthy state.…”
Section: Discussionsupporting
confidence: 88%
“…All foods contained fiber from rice, barley, and sorghum as well as 4.9% beet pulp, with the amount of rice adjusted to accommodate for the added betaine, scFOS, and oat beta-glucan. All foods were in dry form and met the Association of American Feed Control Officials (AAFCO) maintenance nutrition requirements through testing, and dietary analysis was carried out as previously described [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of feeding fiber to cats with CKD, as well as the best type of fiber to feed, have not been well studied. Because the type of fermentable fiber fed influences fecal microbial composition [10], we hypothesized that concentrations of microbiota-generated toxins and their precursor metabolites may be altered in the feces.…”
Section: Introductionmentioning
confidence: 99%